GE_GERICHTE C/5258/2009 vom 14. Dezember 2012 - GE Cour de justice (2012)
; CONTRAT D'ENTREPRISE ; PRIX DE L'OUVRAGE ; HYPOTHÈQUE LÉGALE ; OBSERVATION DU DÉLAI | CO.77 CO.78 CO.132 CO.373 CO.374 CC.8 CC.561.1.1 CC.839.2